Chemistry of 2-dimensional materials: beyond graphene : online virtual event, 23-25 November 2020 - Simpson, Anna (Faraday discussions, 2021)
Spiers Memorial Lecture. Carbon nanostructures by macromolecular design: from branched polyphenylenes to nanographenes and graphene nanoribbons /Zijie Qiu, Akimitsu Narita and Klaus Müllen --Enhanced liquid phase exfoliation of graphene in water using an insoluble bispyrene stabiliser /Yuyoung Shin, Xavier Just-Baringo, Matthew Boyes, Adyasha Panigrahi, Marco Zarattini, Yingxian Chen, Xinyun Liu, Gareth Morris, Eric Prestat, Kostas Kostarelos, Sandra Vranic, Igor Larrosa and Cinzia Casiraghi --Low-energy electron irradiation induced synthesis of molecular nanosheets: influence of the electron beam energy /Christof Neumann, Richard A. Wilhelm, Maria Küllmer and Andrey Turchanin --The philosophy of carbon: meso-entropy materials /Boxu Feng and Xiaodong Zhuang --Additions and corrections --Printable hexagonal boron nitride ionogels /Woo Jin Hyun, Lindsay E. Chaney, Julia R. Downing, Ana C. M. de Moraes and Mark C. Hersam --Multifunctional coatings of exfoliated and reassembled graphite on cellulosic substrates /Leandra Pereira Santos, Douglas Soares da Silva, João Paulo Ferreira Bertacchi, Kelly Schneider Moreira, Thiago Augusto Lima Burgo, Bruno Carreira Batista, Jeferson dos Santos,Patrick Alvarenga de Paula and Fernando Galembeck --Sol-gel synthesis of 2-dimensional TiO₂: self-assembly of Ti-oxoalkoxy-acetate complexes by carboxylate ligand directed condensation /Ruohong Sui, Connor E. Deering, Rohen Prinsloo, Christopher B. Lavery, Nancy Chou and Robert A. Marriott --2D materials production and generation of functional inks: general discussion --Raman spectroscopy of GaSe and InSe post-transition metal chalcogenides layers /Maciej R. Molas, Anastasia V. Tyurnina, Viktor Zólyomi, Anna K. Ott, Daniel J. Terry, Matthew J. Hamer, Celal Yelgel, Adam Babiński, Albert G. Nasibulin, Andrea C. Ferrari, Vladimir I. Fal'ko and Roman Gorbachev --Stability and universal encapsulation of epitaxial Xenes /Alessandro Molle, Gabriele Faraone, Alessio Lamperti, Daniele Chiappe, Eugenio Cinquanta, Christian Martella, Emiliano Bonera, Emilio Scalise and Carlo Grazianetti --Applications in opto-electronics: general discussion --Biodegradation of graphene materials catalyzed by human eosinophil peroxidase /Rajendra Kurapati, Cristina Martin, Vincenzo Palermo, Yuta Nishina and Alberto Bianco --White graphene quantum dots as electrochemical sensing platform for ferritin /Mayang Garg, Reetu Rani, Amit L. Sharma and Suman Singh --Autoperforation of two-dimensional materials to generate colloidal state machines capable of locomotion /Albert Tianxiang Liu, Jing Fan Yang, Lexy N. LeMar, Ge Zhang, Ana Pervan, Todd D. Murphey and Michael S. Strano --DNA-driven dynamic assembly of MoS₂ nanosheets /Giuseppe Amoroso, Andrei Sapelkin, Qingyu Ye, Vicente Araullo-Peters, Alessandro Cecconello, Gustavo Fernandez and Matteo Palma --Biomedical applications: general discussion --Graphene-supported 2D cobalt oxides for catalytic applications /Loïc Michel, Sécou Sall, Thierry Dintzer, Cerise Robert, Antoine Demange and Valérie Caps --Core-shell graphene oxide-polymer hollow fibers as water filters with enhanced performance and selectivity /Alessandro Kovtun, Antonio Bianchi, Massimo Zambianchi, Cristian Bettini, Franco Corticelli, Giampiero Ruani, Letizia Bocchi, Francesco Stante, Massimo Gazzano, Tainah Dorina MArforio, Matteo Calvaresi, Matteo Minelli, Maria Luisa Navacchia, Vincenzo Palmero and Manuela Melucci --Electrochemical exfoliation of graphite in H₂SO₄, Li₂SO₄ and NaClO₄ solutions monitored in situ by Raman microscopy and spectroscopy /Zhenyuan Xia, Vittorio Bellani, Jinhua Sun and Vincenzo Palermo --Graphitic carbon nitrides as platforms for single-atom photocatalysis /Felippe M. Colombari, Marcos A. R. da Silva, Mauricio S. Homsi, Beatriz R. L. de Souza, Milenny Araujo, Juliana L. Francisco, Gelson T. S. T. da Silva, Ingrid F. Silva, André F. de Moura and Ivo F. Teixeira --Facile assembly of layer-interlocked graphene heterostructures as flexible electrodes for Li-ion batteries /Gang Wang, Guangbo Chen, Sheng Yang, Panpan Zhang, Faxing Wang, Ibrahim Bozkurt, Hyeon Suk Shin, Hu Young Jeong and Manish Chhowalla --Computational design of graphitic carbon nitride photocatalysts for water splitting /Gareth O. Hartley and Natalia Martsinovich --3-dimensional graphene-like structures and applications: general discussion --Concluding remarks: chemistry of 2-dimensional materials: beyond graphene /Alessandro Silvestri, Alejandro Criado and Maurizio Prato.